Pemetaan Permasalahan Struktural Bantuan Sosial Di Indonesia - Amrie Firmansyah; Dewi Darmastuti (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2026)
This study aims to map and synthesize social assistance problems in Indonesia based on the Audit Board of the Republic of Indonesia (BPK) Semester Audit Summary Reports (IHPS) for Semester II, covering the period 2020-2024. A scoping review approach was employed to identify recurring issues, key problem clusters, and interlinkages across the governance cycle of social assistance programs. The primary data source consists of IHPS BPK documents, while supporting evidence was drawn from academic articles selected through systematic inclusion and exclusion criteria, resulting in ten core articles for thematic synthesis. The analysis reveals that social assistance problems are recurrent and persistent, encompassing targeting inaccuracies, weaknesses in beneficiary data management, implementation challenges, deficiencies in distribution mechanisms, and ineffective internal controls and oversight. The synthesis indicates that these issues are interconnected and reflect structural weaknesses in social assistance governance rather than isolated technical or administrative shortcomings. The findings suggest that improvements in social assistance programs require a systemic governance approach, including strengthening beneficiary data systems, enhancing institutional coordination, improving operational management, and reinforcing risk-based oversight mechanisms. In practice, this study provides policy-relevant insights for policymakers and public-sector stakeholders to design more accountable and sustainable social assistance governance frameworks in Indonesia.